2009
DOI: 10.1097/aco.0b013e3283303884
|View full text |Cite
|
Sign up to set email alerts
|

What is new in pediatric traumatic brain injury?

Abstract: As TBI is the leading cause of death in children, research in this area is needed to advance our knowledge of the sequelae after and improve outcomes of children with TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
2
17
1
Order By: Relevance
“…This ongoing development is believed to be why pediatric patients appear to have an advantage over adult patients in some aspects of recovery following TBI [Giza et al, 2009;Johnston, 2009]. Contrary to this 'younger is better' paradigm, follow-up studies have shown that even mild TBI often has long-term behavioral effects, some of which appear to 'come out' with age as patients reach developmental milestones not achieved prior to injury [Giza et al, 2009;Goold and Vane, 2009;Sookplung and Vavilala, 2009]. The diverse neurological and cognitive effects of TBI have been found to have a particularly profound impact on hippocampal and forebrain function [Giza et al, 2009;Kernie and Parent, 2010].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This ongoing development is believed to be why pediatric patients appear to have an advantage over adult patients in some aspects of recovery following TBI [Giza et al, 2009;Johnston, 2009]. Contrary to this 'younger is better' paradigm, follow-up studies have shown that even mild TBI often has long-term behavioral effects, some of which appear to 'come out' with age as patients reach developmental milestones not achieved prior to injury [Giza et al, 2009;Goold and Vane, 2009;Sookplung and Vavilala, 2009]. The diverse neurological and cognitive effects of TBI have been found to have a particularly profound impact on hippocampal and forebrain function [Giza et al, 2009;Kernie and Parent, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…With traumatic brain injury (TBI) as the leading cause of acquired brain injury in both children and adults, elucidating how damage occurs, the brain's response to that injury, and how both might be affected in order to obtain the best possible outcome are of significant clinical relevance [Giza and Prins, 2006;Yu et al, 2008;Giza et al, 2009;Sookplung and Vavilala, 2009]. The study of pediatric brain injury poses unique challenges because the sequelae of these injuries are age dependent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We know that hypothermia reduces global cerebral metabolism, cerebral oxygen demands, lactic acid accumulation, calcium influx in neurocytes, free radicals production, lipid peroxidation, posttraumatic level of excitatory neurotransmitter, inhibition of apoptosis, and lowers the damage of cytoskeletal structure. (5) There is clear evidence of a beneficial effect of induced hypothermia on neurological outcome in patients following cardiac arrest (6,7) or in neonates with hypoxic -ischemic encephalopathy, (8) but things in traumatic brain injury are controversial. (9) In our study we aimed to determine the safety and effectiveness of MIH for pediatric patients after traumatic or posthypoxic brain injury.…”
Section: Introductionmentioning
confidence: 99%